article The role of music education in the formation and development of children's personality: The role of music education in the formation and development of children's personality (Ensino em Perspectivas, 2025)
The purpose of the study is to analyze the role of music education in the process of forming and developing children's personality. The hypothesis is whether music has a positive impact on children's personality development, including emotional intelligence, moral values ​​and creativity? Does bringing music into the educational curriculum promote children's comprehensive development? To clarify the purpose and hypothesis, we conduct a research to clarify the following contents: Theoretical basis of music education and children's personality development; The role of music in developing emotions, morality, creativity and social skills; Current status of music education in schools and families in Vietnam; Proposed solutions to improve the effectiveness of music education. The main research method used is the qualitative method, in addition, we also use a number of other research methods.